Evaluasi Bore Pile Berdasarkan Pile Driving Analyzer (PDA) dan Standard Penetration Test (SPT) - Rendi Hermawan; Athaya Zhafirah (Institut Teknologi Garut, 2026)
The bored pile foundation must pay attention to the safety limit to withstand the load, for this reason it is necessary to evaluate to determine whether the foundation is done in accordance with the initial planning, the purpose of this study is to analyze and compare how much bearing capacity and maximum load acting on the foundation pile based on the results of the Pile Driving Analyzer (PDA) test and the results of the Standard Penetration Test (SPT) method soil test. The analysis method is based on Reese and Wright with no reduction factor from the N-SPT value. Based on the Reese and Wright method, the ultimate bearing capacity Qu = 448.97 tons and the PDA test results of Ru = 335 tons and the calculation of the maximum load on the pile group based on the working load obtained results of 45.41 tons < 218.21 tons. The results of the calculation of the bearing capacity of the PDA and SPT tests show inappropriate results because the value obtained must be twice the plan value and the number of test points must comply with ASTM D-4945 standards.